ANALISA LEAN MANUFACTURING PRODUKSI THERMOPHILE PADA PT X - Putri Manalu, Rosdiana; Prakasa hasibuan, Rizki (LPPM Universitas Putera Batam, 2022)
PT X is one of the companies engaged in Technologies which has 3 departments to carry out the production process. the company experiences waste in the production process in the form of unnecessary waiting and over processing activities. This study aims to Activities that do not have added value (waste) in the production process. This problem is solved Lean manufacturing identifies are not value added by using lean matrix calculation and VSM (Value Stream Mapping). activity based on the following results: research Manufacturing lead time FTC Department Detection line Cycle efficiency of 48.68 and process speed of 864.55 minutes, Process Observations at 89 % minutes of non-value activity 0.060 at process / hour. After analyzing using a Pareto diagram, the type of activity is Press wavegude (Mirror) to enter the cap using a pen manually, and wavegude oven (Mirror) with a temperature of 160°C. The improvement results show a decrease in the value of manufacturing lead time to 839.49 minutes Process Cycle efficiency increases from 91.70% and an increase in process speed to 0.056 processes / hour. A 0.84% ​​increase in the process cycle efficiency value indicates an increase in the ability of the company to produce the goods according to the specified specifications. Decrease in Non-value added 28.8 minutes. A production cycle time value decreased by 25.06 minutes / cycle and a process speed value increased by 0.004 processes / hour indicates that the company's production process is better and faster. The increase in production processes can be seen in the company's average daily production, which used to be the company's total daily production of 3600 units / day. After the repair, the average total daily production increased to 4500 units/day, or an increase of 900 units/day.